The strategy of Regional Medium Term Development Plan policy of Cianjur regency - Denny Aditya Dwiwarman (PINISI Discretion Review, 2021)
The Regional Medium-Term Development Plan (RPJMD) as a mandatory document in the planning process carried out by local governments is one of the vital documents that determines the future development direction of an area. The purpose of this study was to determine the policy evaluation strategy aimed at the Regional Medium Term Development Plan (RPJMD) for the 2011-2016 period, with the locus of Cianjur Regency. The strategy that can be carried out by the Cianjur Regency government refers to the Priority scale pattern which is based on the calculation results of the Analitycal Hierarchy Process (AHP), which essentially follows the pattern; (1) dimension of perception equation, (2) dimension of accuracy, (3) dimension of equalization, (4) dimension of responsiveness. (5) the dimension of adequacy, (6) the dimension of efficiency, (7) the dimension of effectiveness. The results showed that in order to increase people's purchasing power and create a prosperous South Cianjur community, the Regional Government and DPRD of Cianjur Regency are expected to be able to increase synergy, both in the form of coordination and collaboration, especially in relation to the preparation of the Regional Medium-Term Development Plan in the coming period by making road infrastructure development one of the Cianjur Regency Development Missions. This is very important to do, so that road infrastructure development gets serious attention from various stakeholders.